THE IMPACT OF CHANGES IN ROYALTY RATES ON COMPANY PROFITABILITY: A CASE STUDY OF PT BUKIT ASAM TBK - Puspita, M.; Arafiq, R. M.; Gobel, A. P.; Oktarinasari, E.; Amalia, R. (Jurnal Pertambangan, 2025)
In recent years, the Indonesian government has twice amended the regulations regarding coal royalty rates, namely in 2019 and 2022. Based on Government Regulation No. 81 of 2019, coal royalty rates range from 3-7% (open pit) and 2-6% (underground), depending on the calorific value. Following the implementation of Government Regulation No. 26 of 2022, coal royalty rates have undergone significant changes, ranging from 5% to 13.5% depending on the calorific value and the government-set reference coal price. This new policy is deemed risky for reducing profitability due to the increased amount of royalties that must be paid. This study aims to calculate the increase in royalty costs and assess the financial performance of companies in adapting to the policy using the net profit margin (NPM). The results show that in the fourth quarter of 2022, there was a 107.63% increase in royalty costs. However, this increase in royalties did not cause the companies' profitability to decline. The NPM percentage tended to increase during the period from 2020 to 2022, reaching 13.9%, 27.5%, and 30%, respectively. This was partly due to an increase in sales volume and improved coal prices in 2022. Thus, it can be concluded that the increase in sales volume and coal prices during this period had a positive impact in offsetting the rise in royalty rates caused by the implementation of Government Regulation No. 26 of 2022. As a result, PT Bukit Asam, Tbk's NPM continued to show a positive trend during this period.